Different impact of rATG induction on CMV infection risk in D+R– and R+ KTRs. (26th April 2019) - Kaminski, Hannah; Jarque, Marta; Halfon, Mathieu; Taton, Benjamin; Di Ascia, Ludovic; Pfirmann, Pierre; Visentin, Jonathan; Garrigue, Isabelle; Déchanet-Merville, Julie; Moreau, Jean-François; Crespo, Elena; Montero, Nuria; et al.
Abstract: Background: Rabbit antithymocyte globulin (rATG) induction is associated with profound immunosuppression, leading to a higher risk of cytomegalovirus (CMV) infection compared with anti–interleukin 2 receptor antibody (anti–IL-2RA). However, this risk, depending on the baseline CMV serological recipient/donor status, is still controversial. Methods: The CMV DNAemia-free survival between rATG- and anti–IL-2RA–treated patients was analyzed in donor-positive/recipient-negative (D+R−) and recipient-positive (R+) patients in 1 discovery cohort of 559 kidney transplant recipients (KTRs) and 2 independent cohorts (351 and 135 kidney KTRs). The CMV-specific cell-mediated immunity (CMI) at baseline and at different time points after transplantation was assessed using an interferon γ enzyme-linked immunosorbent spot assay. Results: rATG increased the risk of CMV DNAemia in R+ but not in D+R− KTRs. In R+ CMI-positive (CMI+) patients, the CMV DNAemia rate was higher in rATG-treated than in anti–IL-2RA–treated patients; no difference was observed among R+ CMI-negative (CMI−) patients. Longitudinal follow-up demonstrated a deeper depletion of preformed CMV CMI in R+ rATG-treated patients. Conclusions: D+R− KTRs have the highest risk of CMV DNAemia, but rATG adds no further risk. Among R+ KTRs, we described 3 groups, the least prone being R+CMI+ KTRs without rATG, then R+CMI+ KTRs with rATG, and finally R+CMI− KTRs. CMV serostatus, baseline CMV-specific CMI, and induction therapy may lead to personalized preventive therapy in further studies. Abstract : Rabbit antithymocyte globulin induction therapy added no further risk of cytomegalovirus (CMV) infection in donor-positive/recipient-negative kidney transplant recipients, but risk was increased in CMV-positive recipients, particularly those with preformed CMV cell-mediated immunity. Findings may help personalize preventive therapy after transplantation.